Anti-embolic and anti-oxidative effects of a novel (E)-4-amino-N′-(1-(7-hydroxy-2-oxo-2H-chromen-3-yl) ethylidene) benzohydrazide against isoproterenol and vitamin-K induced ischemic stroke - Mnafgui, Kais; Khdhiri, Emna; Ghazouani, Lakhdar; Ncir, Marwa; Zaafouri, Zouhaier; Allouche, Noureddine; Elfeki, Abdelfattah; Ammar, Houcine; Abid, Souhir; Hajji, Raouf (Archives of physiology and biochemistry, 2021)
This study aimed to evaluate the cerebroprotective potential of a novel synthetic coumarin, (E)-4-amino-N′-(1-(7-hydroxy-2-oxo-2H-chromen-3-yl)ethylidene) benzohydrazide noted (HC) against a pharmaceutically induced ischemic stroke in experimental male Wistar rats. Animals were randomly allocated into four groups: control, Stroke, Stroke + Ace (acenocoumarol) and Stroke + HC-treated group for 7 days. Our results showed that stroke group evidenced atrial flutter, significant cardiac hypertrophy (+23%) and increase in plasma level of troponin-T, with disturbance in plasma ionic levels and rise in fibrinogen rate and oxidative damages in heart and brain. Moreover, the histological findings revealed myocardium necrosis, cardiac cavity thrombi and brain injury as compared to normal rats. However, HC-treatment significantly prevents the embolic process, improves cerebral damages and mitigates the oxidative stress markers in stroke rats. Overall, HC is endowed with a thrombolytic potential against MI and stroke in such severe conditions through an anti-vit K (AVK) mechanism.